2010
DOI: 10.11130/jei.2010.25.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Uncertainty and Export Decisions in the UK

Abstract: Using data on UK manufacturing firms, we examine the effects of exchange rate uncertainty on firm decisions on export market entry and export intensity. The use of micro data and new measures of exchange rate uncertainty enable us to test for hysteresis effects in a new way and to test the sensitivity of results to a range of different measures. The results show that exchange rate uncertainty has little effect on firms' export participation but a significant impact on export intensity. We find that industry he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…As result of the 2008 global financial crisis, many export‐oriented economies suffered due to the significant shrinking of consumer demand and rise of local protectionism in the major markets, including the United States and Europe (UNCTAD ). Research has shown macro‐level evidence of firms' declining export performance and intensity (Greenaway, Kneller, and Zhang ), which is consistent with historical patterns that indicate trade decline occurring after economic depression (Grossman and Meissner ). However, to date, there has been less research on the effect of a financial crisis on exporting activities at the level of the firm, especially with respect to small and medium‐sized firms (SMEs).…”
Section: Introductionsupporting
confidence: 67%
“…As result of the 2008 global financial crisis, many export‐oriented economies suffered due to the significant shrinking of consumer demand and rise of local protectionism in the major markets, including the United States and Europe (UNCTAD ). Research has shown macro‐level evidence of firms' declining export performance and intensity (Greenaway, Kneller, and Zhang ), which is consistent with historical patterns that indicate trade decline occurring after economic depression (Grossman and Meissner ). However, to date, there has been less research on the effect of a financial crisis on exporting activities at the level of the firm, especially with respect to small and medium‐sized firms (SMEs).…”
Section: Introductionsupporting
confidence: 67%
“…8 Firm-level exchange rates are defined as either a weighted average of bilateral exchange rates with the firm's export partners in 1990 and 1994 (for exporters), or a weighted average of bilateral exchange rates with the top four export partners of other firms in the same industry (for non-exporters in both 1990 and 1994). The conditional variance of the exchange rate expected at In contrast to Campa (2004), Greenaway et al (2010) find that exchange rate uncertainty 9 affects export intensity among UK manufacturers, but not the export participation decision. Moreover, they suggest that the direction of uncertainty (whether the realised exchange rate is higher or lower than the expected exchange rate) influences the intensive margin effect.…”
Section: Conceptual Frameworkmentioning
confidence: 79%
“…uses the assumption that exchange rate volatility affects export propensity but not export intensity in order to motivate his use of a Heckman two-stage model. However, as noted above, there may be reasons why firms would choose to limit their exposure to a market in the face of exchange rate volatility while not completely withdrawing from that market -a hypothesis we wish to directly test Greenaway et al (2010). instead use simultaneous estimation via maximum likelihood, which they argue is more efficient than a Heckman model.…”
mentioning
confidence: 99%
“…In spite of reports like this, we know little about the effects of exchange rate volatility on individual firms. The few existing studies using data at the firm or establishment level include Campa (), Solakoglu et al (), Greenaway et al () and Héricourt and Poncet (), which examine the effect of exchange rate volatility on exports; Kandilov and Leblebicioğlu (), which analyzes the impact of exchange rate volatility on investment; and Demir () studying the impact of volatility on employment. To the best of our knowledge, no study exists analyzing the impact of exchange rate volatility on imports of intermediate inputs at the micro level.…”
Section: Introductionmentioning
confidence: 99%